Resistance to Degradation and Cellular Distribution are Important Features for the Antitumor Activity of Gomesin - Buri, Marcus V.; Domingues, Tatiana M.; Paredes-Gamero, Edgar J.; Casaes-Rodrigues, Rafael L.; Rodrigues, Elaine Guadelupe; Miranda, Antonio (PLOS ONE, 2013)
Many reports have shown that antimicrobial peptides exhibit anticancer abilities. Gomesin (Gm) exhibits potent cytotoxic activity against cancer cells by a membrane pore formation induced after well-orchestrated intracellular mechanisms. In this report, the replacements of the Cys by Ser or Thr, and the use D-amino acids in the Gm structure were done to investigate the importance of the resistance to degradation of the molecule with its cytotoxicity. [Thr2,6,11,15]-Gm, and [Ser2,6,11,15]-Gm exhibits low cytotoxicity, and low resistance to degradation, and after 24 h are present in localized area near to the membrane. Conversely, the use of D-amino acids in the analogue [D-Thr2,6,11,15]-D-Gm confers resistance to degradation, increases its potency, and maintained this peptide spread in the cytosol similarly to what happens with Gm. Replacements of Cys by Thr and Gln by L- or D-Pro ([D-Thr2,6,11,15, Pro9]-D-Gm, and [Thr2,6,11,15, D-Pro9]-Gm), which induced a similar β-hairpin conformation, also increase their resistance to degradation, and cytotoxicity, but after 24 h they are not present spread in the cytosol, exhibiting lower cytotoxicity in comparison to Gm. Additionally, chloroquine, a lysosomal enzyme inhibitor potentiated the effect of the peptides. Furthermore, the binding and internalization of peptides was determined, but a direct correlation among these factors was not observed. However, cholesterol ablation, which increase fluidity of cellular membrane, also increase cytotoxicity and internalization of peptides. β-hairpin spatial conformation, and intracellular localization/target, and the capability of entry are important properties of gomesin cytotoxicity.